KEPEMIMPINAN KOLABORASI KEPALA SEKOLAH DALAM MEMBANGUN TIM KINERJA GURU DI ERA SOCIETY 5.0 - Dakabesi, Eklopas Dakabesi; Wicaksono, Luhur (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The challenges of education in the era of society 5.0 cannot be avoided by any organization, including schools in Indonesia, where schools are not only required to strive for their existence but are also obliged tochange the paradigm of thinking about leadership styles that are relevant to the formation of a team of teachers who are as friendly, littery and in line with the goals of national education. Responding to this challenge requires a lot of thought and contribution from a solid team of educators in the school, namely a team whose leadership model expands the collaboration space for every personnel in the school. This research is important because it aims to test and understand the ability of collaborative leadership in facing educational challenges in the era of society 5.0, in order to be able to build a solitary team of teacher work that meets community expectations. The author uses a qualitative research approach, with library research as a method of document analysis with narrative research and techniques for processing thematic data. Collaboration is one of the principles of the 4 Cs of life skills (Creativity, Critical Thingking, Communication, Collaboration) which is required to be possessed by principals and teachers in building their work teams in facing challenges in the 21st century society 5.0. Theprincipal collaboration leadership is a model or leadership style needed by schools in building teacher togetherness to meet educational needs in the 21st century society 5.0..